Influence of oxygen partial pressure on SrTiO3 bulk crystal growth from non-stoichiometric melts. Issue 17 (7th May 2015) - Guguschev, Christo; Kok, Dirk J.; Galazka, Zbigniew; Klimm, Detlef; Uecker, Reinhard; Bertram, Rainer; Naumann, Martin; Juda, Uta; Kwasniewski, Albert; Bickermann, Matthias
<x xml:space="preserve">Abstract</x> Tausonite (SrTiO3) single crystals grown by the top-seeded solution growth method.